Political Economy of Religious and Cultural Symbols in the Soap Opera of Tukang Bubur Naik Haji At RCTI - Yasir Yasir (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
Television is a very influential media and important tool in capital accumulation. This study aims to reveal the use of Islamic and Betawi ethnic symbols, workers, and also the audiences of Tukang Bubur Naik Haji (TBNH) soap opera at RCTI. This research used a political economy of communication perspective. The data were collected by using interview, observation, documentation, and literature study. The result shows that the religious symbols of Islam and Betawi culture have been exploited as comodity to be traded. Those symbols have been commercialized dan manipulated through the use of sensational, provocative, and hyperbole words or sentences to entertain audiences and to attract the advertisers. The hyper-comercialization and politicization of symbols caused the soap opera workers and Moslem audiences have been exploited.